Novel FRET-substrates of Rhizomucor pusillus rennin: Activity and mechanistic studies. (15th April 2018) - Stergiou, Panagiota-Yiolanda; Foukis, Athanasios; Gkini, Olga A.; Barouni, Eleftheria; Georgoulia, Panagiota S.; Kanellaki, Maria; Koutinas, Athanasios A.; Papagianni, Maria; Papamichael, Emmanuel M.
Highlights: Computational simulation studies of MPR specificity along with potential substrates. Analysis of individual MPR-substrate interactions (MD and metadynamics simulations). Design and synthesis of specific FRET-substrates for MPR. Kinetic characterization of MPR and elucidation of its detailed mechanism of action. Sensitive and reliable MPR's activity methods (as free in solution and immobilized). Abstract: The development of sensitive, easy and reliable methods for the determination of Rhizomucor pusillus rennin (MPR) activity, in free and in immobilized form, along with the elucidation of the mechanism of action, represent challenges for the widespread use of the enzyme in industrial cheese production. These could be accomplished by using highly specific and sensitive substrates, as well as direct assay methods. We designed and synthesized novel substrates based on Fluorescence Resonance Energy Transfer (FRET) for the MPR by employing computational simulation techniques and peptide synthesis in liquid phase. Three FRET-substrates (Abz-GFY-pNA, Abz-SFY-pNA and Abz-GFI-pNA) were found active, while the Abz-GFY-pNA showed the highest reliability, sensitivity and specificity among them. Subsequently, a novel mechanism of MPR action was elucidated, with the development of novel methods for assaying activity in free and immobilized form, which both may contribute in the wider use of rennin in cheese production and other biotechnological applications.